1980
DOI: 10.1128/jcm.12.5.672-675.1980
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in density of cutaneous propionibacteria: correlation of Propionibacterium acnes populations with sebaceous secretion

Abstract: Cutaneous Propionibacterium acnes populations were quantitatively measured in 33 young adults and compared with the rate and composition of sebum secretion in nine skin regions. Bacteriological and lipid analyses were performed on the forehead, cheek, anterior chest, abdomen, lower back, volar forearm, upper inner arm, thigh, and calf. P. acnes populations in these sites correlated significantly with the total amount of lipid produced (r = 0.77) as well as with di- and triglycerides (r = 0.68), squalene and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 5 publications
3
49
0
1
Order By: Relevance
“…In the present study, squalene has been shown to be a highy effective oxygen-trapping compound. This agrees with previous findings where a positive correlation was found between quantities of sebum and colonization by propionibacteria, on different skin sites (McGinley et al, 1980). Such a close link in the light of the findings reported here suggests the need for reappraisal of the role of sebum, a long debated question (Kligman, 1963), as squalene would appear to be the factor which may control the colonization of the skin by micro-aerophilic flora.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, squalene has been shown to be a highy effective oxygen-trapping compound. This agrees with previous findings where a positive correlation was found between quantities of sebum and colonization by propionibacteria, on different skin sites (McGinley et al, 1980). Such a close link in the light of the findings reported here suggests the need for reappraisal of the role of sebum, a long debated question (Kligman, 1963), as squalene would appear to be the factor which may control the colonization of the skin by micro-aerophilic flora.…”
Section: Discussionsupporting
confidence: 93%
“…From a bacteriological point of view, the porphyrins have been clearly sbown to be synthesized in vivo by Propionibacierium spp. (Cornelius & Ludwig, 1967;McGinley, et al, 1980). We hypothesize tbat occurrence of porphyrins in vivo could be due to their biosynthesis by propionibacteria in response to raised oxygen tension within the pilo sebaceous duct.…”
Section: Discussionmentioning
confidence: 85%
“…The results of the microbial colonization of the skin surface and follicular casts in the three groups of patients we have investigated are consistent with previous data in terms of dominance of microbial types at different skin sites, 3,29,32±34 the preferential location of the aerobic coryneforms and micrococci to the skin surface compared with follicular casts, 35 and the low incidence of these bacteria on the face and back. 36 The prevalence, dominance and population densities of the skin microorganisms at acne sites have been explained by the influence of the SER, 34,37 and a higher SER on the face of female patients with persistent acne compared with control individuals supports this hypothesis, 38 although a higher SER does not necessarily accompany a higher microbial population density at the skin site. 39 The microbial numbers at the subsurface location may be determined, in part, by local anatomical follicular differences, producing variations in suitable microenvironmental niches in different body sites and/or individuals.…”
Section: Discussionmentioning
confidence: 89%
“…The regional distribution of the organism Propionibacterium acnes is widely distributed on the adult human skin, hair, oropharynx and gastrointestinal tract (Willis 1977;Brook and Frazier 1991), and is considered to cause skin disorders and acne. T h e organism is found on the oily areas of the skin such as the scalp and forehead, and is present, to a lesser degree, on the drier skin areas like arms and legs (McGinley et al 1978(McGinley et al , 1980. Furthermore, it can be found at all levels of the pilo-sebaceous duct and on the skin surface (Holland et al 1977;Kearney et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Within microbiology, this technique, called pyrolysis mass spectrometry (PyMS), has largely been applied to the characterization of bacterial systems (for reviews see Meu-zelaar et al 1982;Gutteridge 1987;Berkeley et al 1990). In particular, because of its high discriminatory ability, PyMS has been successfully applied to the inter-strain comparison of a wide range of medically-important bacterial species and groups, including Corynebacterium (Meuzelaar et al 1982), Escherichia coli (Goodacre et al 1991), Legionella (Kajioka and Tang 1984), mycobacteria (Wieten et al 1981a, b), salmonellas (Freeman et al 1990) and streptococci (Magee et al 1991), highlighting the usefulness of the technique in the detection of small differences between microbial samples. One of the major advantages that PyMS has over other diagnostic methods, such as ELISA (Chantler and McIllmurray 1987) and nucleic acid probing (Saano and Lindstrom 1990), is that it is rapid, both for a single sample and in the (automated) throughput of samples.…”
Section: Introductionmentioning
confidence: 99%